PHYSIOLOGICAL AND HEALTH EFFECTS OF WINTER SWIMMING: A COMPREHENSIVE MEDICAL REVIEW - Kacper Gryboś; Weronika Sepioło; Ilona Boniakowska; Ilona Kamińska; Maria Wydra; Jakub Przerwa; Joanna Wąsik; Izabela Stachowicz; Eliza Gawron; Julia Samborska; Anna Łysik (International Journal of Innovative Technologies in Social Science, 2025)
Winter swimming, defined as immersion in cold water, is gaining popularity as a form of physical activity and a natural health-enhancing intervention. This article provides a comprehensive medical review of the physiological and health effects associated with cold water exposure. Acute bodily responses to cold immersion are discussed, including activation of thermoregulatory mechanisms, cardiovascular, respiratory, and neuromuscular changes, as well as the risks of hypothermia and cold shock. Chronic adaptations observed in regular winter swimmers are also presented, encompassing hormonal, metabolic, and immunological modifications that enhance cold tolerance and support homeostasis. The health benefits of winter swimming are analyzed, highlighting improvements in cardiovascular performance, immune system modulation, mood enhancement, and metabolic regulation. Concurrently, potential risks are emphasized, particularly for individuals with chronic illnesses, children, and the elderly. The article concludes with a comparative analysis of winter swimming and other cold therapies, noting differences in exposure intensity and therapeutic efficacy. This review underscores the need for further research to standardize protocols and better elucidate the long-term effects of winter swimming.